Kajian Fenomenologi tentang Kinerja Berorientasi Individu dalam Ilmu Amaliah pada Yayasan Wakaf Universitas Muslim Indoesia - Darwis Lannai (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
This study used a qualitative intrepretif paradigm in the study of phenomenology which describes the relationship between action and meaning. Measures refers to several things and meaning not only find, but the interpretation of active and disciplined. Interpretation Creative to ensure the possibility of action meaning and message. Action and meaning in an effort to understand the indivdual performance. Individual performance in the foundations need to study in depth because it is very different from the characteristics of other organizations. This study is to formulate how the meaning of an individual's performance on the YW-UMI to find the meaning of the performance of the YW-UMI. Looked at narrowly performance is only noticed aspects of shareholder interests and ignoring the interests of other causes not achieving the purpose of the foundation is to salvation people. Solutions to interpret the performance of the performance paradigm must be built for the benefit of the people. Oriented interests for the benefit of the individual, social, and spiritual. Our research found meaning in the knowledge amaliah performance on the Foundation Waqf Indonesia Muslim University (YW-UMI). Meaning an individual's nature in carrying out the activities of the foundation. Amaliah knowledge was reflected in the individual nature of YW-UMI. Individual properties are referred to as STAFH (Siddiq, Tabliqh, Amanah, Fathonah, and Himayah).